Mouse amyloid protein AA: Homology with nonimmunoglobulin protein of human and monkey amyloid substance. - Eriksen, N (1976)
The major protein extracted from anyloid deposits induced in mice by injection of either Candida albicans cells or sodium caseinate was found to have chromatographic and electrophoretic properties and an amino-acid compostiion characteristic of the AA class of amyloid proteins. The homology of the mouse protein with protein AA from man and monkey was established by determination of the sequence of the first 28 amino-acid residues.